Finite Element Analysis of New Designed Intercalary Prosthesis Implant (Ulna Bone) - Mustafa, Sadeer Anwer; Shammari, Ahmed Z. M.; Augla, Wmieth A. J.; Mohammed, M. N. (Al-Khwarizmi Engineering Journal, 2024)
Implantation via an intercalary prosthetic method is a reliable solution for reconstructing a long defect in bones that has been damaged by severe disease or accidents. In the current study, using data from computed tomography (CT) scans, a novel costumed intercalary prosthesis design has been created. To achieve this purpose, the CT scan data of a patient in (DICOM) file format was converted into computer-aided design models and saved in stereolithography (STL) format using the 3D slicer (5.0.3) software. The STL files were loaded into Meshmixer software to design the models of the intercalary prosthesis. Finite element analysis (FEA) was applied to validate the strength of the prosthesis with impact, tensile testing, and torsional testing. According to the results of the impact tests, the highest recorded deformation was 8.8485e-002 m in the area where the implant body interfaces with the bone intramedullary canal, due to the high-stress (Von Mises Stress) value of 3.78 E9 PA. In the torsional loaded the highest deformation recorded was 1.3871e-008 m when the Von Mises stress reached 49006 PA, and with the application of the tensile test the largest deformation measured as 1.0458e-006 m at maximum Von Mises stress seen was recorded as 6.6012e+006 PA which caused that. A solid rod of Ti6Al4V alloy was selected. Finally, the analysis proved that the implant had enhanced mechanical properties. Based on the findings, it can be inferred that the prosthesis was successfully implanted, and a satisfactory result was obtained by using this design method.